2022
DOI: 10.1002/eem2.12296
|View full text |Cite
|
Sign up to set email alerts
|

Surface Passivation Toward Efficient and Stable Perovskite Solar Cells

Abstract: Although metal halide perovskites are increasingly popular for the next generation of efficient photovoltaic devices, the inevitable defects from the preparation process have become the notorious barrier to further improvement of performance, which increases non‐radiative recombination and lowers the power conversion efficiency of solar cells. Surface passivation strategies have been affirmed as one of the most practical approaches to suppress these defects. Therefore, it is necessary to have a detailed review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 130 publications
0
47
0
Order By: Relevance
“…Metal halide perovskite materials with excellent photoelectric properties have become the promising materials for the next generation of solar cells [406,407]. The high defect tolerance is the one reason for its excellent carrier transport and peculiar recombination properties [228].…”
Section: Interfacial Functional Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal halide perovskite materials with excellent photoelectric properties have become the promising materials for the next generation of solar cells [406,407]. The high defect tolerance is the one reason for its excellent carrier transport and peculiar recombination properties [228].…”
Section: Interfacial Functional Materialsmentioning
confidence: 99%
“…Secondly, based on multi-quantum well structure, low-dimensional perovskite has unique exciton properties, and the "edge state" can dissociate excitons into long-lived free carriers directly, and then promote the carrier transport. Finally, wide-band gap 2D perovskite can also optimize the energy level structure, promote band alignment (Figure 29), passivate defects, reduce the density of defect state, and inhibit the ion migration [407]. Lowdimensional perovskites can be formed in situ on the top surface of perovskites, which greatly simplifies the process of forming heterojunctions.…”
Section: Forming Junction Materialsmentioning
confidence: 99%
“…Surface passivation is a widely adopted strategy to modify the interfaces between the CTL and perovskite. [ 15 , 16 , 17 , 18 ] It has been reported that organic materials with electron‐rich carbonyl or amino functional groups can effectively passivate the under‐coordinated metal ions, contributing to improved device efficiency. [ 19 , 20 , 21 , 22 , 23 ] For example, Qiu et al.…”
Section: Introductionmentioning
confidence: 99%
“…12−15 Generally, the 2D perovskite could be described by the formula (A′) 2 (A) n−1 M n X 3n+1 , where A stands for a monovalent cation (e.g., Cs + , MA + , FA + ), M is a divalent metal cation (e.g., Pb 2+ , Sn 2+ ), X represents a halide anion (e.g., Cl − , Br − , I − ), and A′ is normally an large ammonium cation organic spacer such as BA + (butylamine: C 4 H 11 N) and PEA + (phenylethylammonium: C 8 H 12 N). 16 Since the M n X 3n+1 inorganic layers are intrinsically separated by the insulating intercalated A′ ions with finite electronic barriers, the 2D Ruddlesden−Popperphase perovskite acts as natural multiple quantum wells. 17 The thickness of the 2D layers is defined by the n value, which regulates the electronic and optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to MoS 2 , a 2D Ruddlesden–Popper (RP) metal halide perovskite is regarded as another emerging layered material with strikingly different structural and electronic properties that enable tunable optoelectronic properties and a high degree of structural flexibility. Generally, the 2D perovskite could be described by the formula (A′) 2 (A) n −1 M n X 3 n +1 , where A stands for a monovalent cation (e.g., Cs + , MA + , FA + ), M is a divalent metal cation (e.g., Pb 2+ , Sn 2+ ), X represents a halide anion (e.g., Cl – , Br – , I – ), and A′ is normally an large ammonium cation organic spacer such as BA + (butylamine: C 4 H 11 N) and PEA + (phenylethylammonium: C 8 H 12 N) . Since the M n X 3 n +1 inorganic layers are intrinsically separated by the insulating intercalated A′ ions with finite electronic barriers, the 2D Ruddlesden–Popper-phase perovskite acts as natural multiple quantum wells .…”
Section: Introductionmentioning
confidence: 99%